FOOD PIGMENTS: NUTRACEUTICAL COMPOUNDS WITH MULTIFUNCTIONS - JESSIE SUNEETHA W, K. B. NIRMALA; G. SWARUPA RANI (The Journal of Research, PJTSAU, 2026)
Natural pigments are compounds responsible for the diverse colours observed in living organisms, ranging from red, orange, yellow, green, blue and purple to brown and black shades. In raw and unprocessed foods, these pigments enhanced visual appeal and strongly influenced consumer perception of freshness, quality and acceptability. Natural pigments are widely distributed in plants, animals and microorganisms like algae, fungi and yeasts. Besides contributing to colour, these compounds perform numerous essential biological functions. In nature, pigments often act as attractants or mating signals helping organisms communicate and reproduce successfully. In some species, coloration provided camouflage and protection against predators. Several pigments also played critical physiological and metabolic roles. For example, chlorophylls and carotenoids are directly involved in photosynthesis, energy generation and biosynthetic pathways. Other pigments function as antioxidants, protecting biomolecules from oxidative damage caused by reactive oxygen species. Certain compounds are involved in vision, while others protect skin and cellular membranes from harmful effects of sunlight and radiation. Because of their multifunctional roles, interest in natural pigments extends beyond their colouring properties. In recent years, increasing attention has been given to their nutraceutical and functional benefits, including antioxidant, anti-inflammatory and health-promoting effects. Alongside natural pigments, synthetic and microbial food colourants are also widely used in the food industry to improve appearance and consumer appeal. However, concerns regarding the safety and health impacts of some synthetic pigments have encouraged greater research and utilization of natural alternatives. Therefore, natural, synthetic and microbial food pigments continue to be important not only for enhancing food aesthetics but also for their potential effects on human health and wellbeing.